PENERAPAN QUALITY EVALUAION METHOD (QEM) PADA EVALUASI - Fendri Martadinata (jurnal kesehatan terapan sains dan teknologi, 2023)
In general, the city government website is pretty good. The need to evaluate existing web pemerinahan city on accessing the website used easily by the public and by various types of web browsers, search engines use the content and the content of the web site if the city government is based reference guide to the implementation of local government web sites, therefore the website Urban Governance in South Sumatra province should be measured based on criteria of accessibility, speed, navigability and site content based on quality evaluation method (QEM). Sampelyang used 100 respondents, measurement Likert scale. In the study conducted was obtained result is the quality of Palembang City Government Web site of 3.1, by 3.6 Prabumulih City, City of Pagar Alam by 3.1 and by 3.3 Linggau Lubuk City. Value above that of the highest value sites and the lowest we Prabumulih city of Palembang city website and city of Pagar Alam, while the assessment of internval score it can be concluded that the quality of government websites Palembang in South Sumatra is pretty good.